A Randomized controlled trial to evaluate the impact of a Nurse Navigator Programme on outcomes of people with breast cancer: study protocol. (1st December 2016) - Chillakunnel Hussain Rawther, Shejila; Pai, Mamatha Shivananda; Fernandes, Donald J; Mathew, Stanley; Binu, V S; Chakrabarty, Jyothi; Devi, Elsa Sanatombi; George, Anice; Nayak, Baby S
Abstract: Aim: To evaluate the effectiveness of a Nurse Navigator Programme on anxiety, psychological distress and quality of life in people with breast cancer. Background: Breast cancer is the most frequently detected malignancy and a major cause of cancer death among women around the world. The lengthy course of illness from initial diagnosis to treatment and subsequent follow‐up causes deterioration in physical, psychological and social status among patients. Nurses have a major role in cancer care. As women with breast cancer have to undergo various treatment modalities, continued care by a pivot nurse is thought to enhance treatment adherence. Limited studies have been reported from developing countries on Nurse Navigation Programmes. Design: A Stratified Randomized controlled trial with repeated measures. Methods: One hundred and twenty newly diagnosed women with breast cancer admitted to surgery wards of a tertiary care hospital in South India will be recruited. (Project funded in Octo"ber 2014). Women are randomly allocated to a control and intervention group. The outcome variables are anxiety, psychological distress and quality of life. Data on outcome measures will be collected at five different time points: before surgery, at discharge, beginning of adjuvant therapy, middle of adjuvant therapy and at the end of adjuvant therapy. Discussion: This study may give evidence on the effectiveness of a Nurse Navigator Programme for women with breast cancer. If significant effects were detected, the programme could be integrated into hospital services to improve the patient care.